On the inflection of Polish female and male surnames and their description in the Grammatical Dictionary of Polish - Bronk, Zbigniew; Saloni, Zygmunt (Papers in Linguistics, 2019)
The problem of nouns referring to people of specific sex is recently in fashion – it is discussed in many languages. In Polish the grammatical category of gender (based on sex) is very important (in contrast to English): each noun must be masculine, feminine, or neuter. However, the masculine and feminine genders are not always used according to the sex of the person. The use of the masculine nouns for women is particularly frequent, but female derivatives of them are also used, both traditional or newly created. Names for which the possibility of reference to people of both sexes is equal are surnames. The surname is the common name of family members; in Poland, it has been passed on to the children by the father (or the mother), to the wife – by the husband, now it is possible to take the surname also from the wife. In Polish, like in many other languages, the form of a surname differs for male and female members of the family. Although intuitively the surname of a man and a woman (e.g. siblings, children of the same parents) is the same entity, dictionaries or lists record separately two names of the type Kowalski and Kowalska – as two lexemes, differently declined by case and number. We have adhered to this solution in the Grammatical Dictionary of Polish (SGJP), which we have recently enriched with common Polish surnames. We have systematically introduced surnames that, according to the PESEL (the national identification number) database, have at least 50 representatives of one sex, as well as individual names less frequent but generally known (including surnames of people of other nationalities). According to the general rules of the SGJP, their variation was indicated (a surname having one nominative form, e.g. Mickiewicz or Chopin, declines differently in masculine and feminine) together with variants, as well as the correspondence between male and female versions of a surname.